Reversal of mitochondrial permeability transition pore and pancreas degeneration by chloroform fraction of Ocimum gratissimum (L.) leaf extract in type 2 diabetic rat model - Salemcity, A. J.; Olanlokun, John Oludele; Olowofolahan, A. O.; Olojo, F. O.; Adegoke, Ayodeji Mathias; Olorunsogo, O. O. (Frontiers in Pharmacology, 2023)
Unmanaged Diabetes Mellitus (DM) usually results to tissue wastage because of mitochondrial dysfunction. Adverse effects of some drugs used in the management of DM necessitates the search for alternative therapy from plant origin with less or no side effects. Ocimum gratissimum (OG) has been folklorically used in the management of DM. However, the mechanism used by this plant is not fully understood. This study was designed to investigate the effects of chloroform fraction of OG leaf (CFOG) in the reversal of tissue wastage in DM via inhibition of mitochondrial-mediated cell death in streptozotocin (STZ)-induced diabetic male Wistar rats. Air-dried OG leaves were extracted with methanol and partitioned successively between n-hexane, chloroform, ethylacetate and methanol to obtain their fractions while CFOG was further used because of its activity. Diabetes was induced in fifteen male Wistar rats, previously fed with high fat diet (28 days), via a single intraperitoneal administration of STZ (35mg/kg). Diabetes was confirmed after 72 hours. Another five fed rats were used as the normal control, treated with corn oil (group 1). The diabetic animals were grouped (n=5) and treated for twenty-eight days as follows: group 2 (diabetic control: DC) received corn oil (10 mL/kg), groups 3 and 4 were administered 400mg/kg CFOG and 5mg/kg glibenclamide, respectively. Body weight and Fasting Blood Glucose (FBG) were determined while Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) and beta cell (HOMA-β), and pancreatic tissue regenerating potential by CFOG were assessed. Activity-guided purification and characterization of the most active principle in CFOG was done using chromatographic and NMR techniques. The animals were sacrificed after twenty-eight days, blood samples were collected and serum was obtained. Liver mitochondria were isolated and mitochondrial permeability transition (mPT) was investigated by spectrophotometry. CFOG reversed diabetic-induced mPT pore opening, inhibited ATPase activity and lipid peroxidation. CFOG reduced HOMA-IR but enhanced HOMA-β and caused regeneration of pancreatic cells relative to DC. Lupanol was a major metabolite of CFOG. Normoglycemic effect of CFOG, coupled with reversal of mPT, reduced HOMA-IR and improved HOMA-β showed the probable antidiabetic mechanism and tissue regenerating potentials of OG.